Gotong Royong dalam Festival Sindoro Sumbing - Fawarti Gendra Nata Utami (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2022)
The Sindoro Sumbing Festival is part of the Indonesiana Platform. The Mapageh Sang Watu Kalumpang ballet is the core of the cultural event series Sindoro-Sumbing Festival (FSS) 2019 which took place at Kledung Field, Temanggung. This annual festival was held for the first time on 19 and 20 July 2019. It is a collaboration of the governments of Wonosobo and Temanggung Regencies that promoted local wisdom and environment friendly through a creative approach. The Sindoro Sumbing Festival is a mutual cooperation platform in strengthening the governance capacity of cultural activities as well as a forum for strengthening the cultural ecosystem. It shows how the synergy between the local government, in this case the Culture Office, with the community/artist and the cultural ecosystem in the area in collaboration with the UPT (Technical Implementing Unit), the Ministry of Education and Culture in the area such as the Archaeological Center, Museums, Cultural Conservation Center as well as various institutions, companies, CSR in each region. The Indonesiana Platform is expected to be a working model for organizing cultural arts festivals an various parts of the country.